Subthalamic nucleus but not entopeduncular nucleus deep brain stimulation enhances neurogenesis in the SVZ-olfactory bulb system of Parkinsonian rats - Fauser, Mareike; Payonk, Jan Philipp; Weber, Hanna; Statz, Meike; Winter, Christine; Hadar, Ravit; Appali, Revathi; van Rienen, Ursula; Brandt, Moritz D.; Storch, Alexander (Frontiers in Cellular Neuroscience, 2024)
Deep brain stimulation (DBS) is a highly effective treatment option in Parkinson's disease. However, the underlying mechanisms of action, particularly effects on neuronal plasticity, remain enigmatic. Adult neurogenesis in the subventricular zone-olfactory bulb (SVZ-OB) axis and in the dentate gyrus (DG) has been linked to various non-motor symptoms in PD, e.g. memory deficits and olfactory dysfunction. Since DBS affects several of these non-motor symptoms, we analysed the effects of DBS in the subthalamic nucleus (STN) and the entopeduncular nucleus (EPN) on neurogenesis in 6hydroxydopamine (6-OHDA)-lesioned hemiparkinsonian rats. In our study, we applied five weeks of continuous bilateral STN-DBS or EPN-DBS in 6-OHDA-lesioned rats with stable dopaminergic deficits compared to 6-OHDA-lesioned rats with corresponding sham stimulation. We injected two thymidine analogues to quantify newborn neurons early after DBS onset and three weeks later. Immunohistochemistry identified newborn cells co-labelled with NeuN, TH and GABA within the OB and DG. As a putative mechanism, we simulated the electric field distribution depending on the stimulation site to analyse direct electric effects on neural stem cell proliferation. STN-DBS persistently increased the number of newborn dopaminergic and GABAergic neurons in the OB but not in the DG, while EPN-DBS does not impact neurogenesis. These effects do not seem to be mediated via direct electric stimulation of neural stem/progenitor cells within the neurogenic niches. Our data support target-specific effects of STN-DBS on adult neurogenesis, a putative modulator of non-motor symptoms in Parkinson's disease.